TELAAH SOSIOLOGIS TERHADAP NOVEL AKI KARYA IDRUS: CERMINAN MASYARAKAT DALAM KARYA SASTRA - Aina Zulfatun Nisa; Ainisa Liana Putri; Ahmad Supena (Universitas Batanghari, 2025)
Literary criticism is a branch of literary science that specifically describes, examines and evaluates a work of literature. Literary criticism can be done using literary sociology, a multidisciplinary approach between sociology and literature. Literary sociology studies the relationship of literary works to society or culture. Ian Watt's sociology of literature studies literature using three main approaches: the author's social context, literature as a reflection of society, and the social function of literature. This research is a literary criticism that discusses the reflection of society in the novel Aki by Idrus as the object of research. This research uses a descriptive qualitative approach with data collection methods in the form of analysis and literature review. This research aims to find out the reflection of society in each structure of the novel Aki. The results of this study describe literary works as a reflection of society represented by themes, characters, and settings, and present some of the attitudes of the characters in the novel Aki that reflect the current state of society.